Returning to the emergency department: a retrospective analysis of mental health re-presentations among young people in New South Wales, Australia - Rebecca Ivers; Michael Dinh; Patricia Cullen; Bette Liu; Katharine Steinbeck; Natasha Walker; Robert Neil Leong (BMJ Open)
Objectives This study aimed to describe mental health emergency department (ED) presentations among young people aged 8–26 years in New South Wales, Australia, and to identify key characteristics associated with higher risk of ED mental health re-presentation.Design, setting and participants Retrospective analysis of linked ED data records for mental health presentations between 1 January 2015 and 30 June 2018.Main outcome measures The main outcome was the total number of mental health ED re-presentations within 1 year, following initial presentation. Count regression models were fitted to estimate factors associated with higher likelihood of re-presentations.Results Forty thousand two hundred and ninety patients were included in the analyses, and 9713 (~25%) re-presented during the following year; 1831 (20%) presented at least three times. On average, patients re-presented 0.61 times per 365 person-days, with average time until first re-presentation of ~92 days but greatest risk of re-presentation within first 30–60 days. Young people with self-harm or suicidal diagnoses at initial presentation were more likely to re-present. Re-presentations were highest among young people <15 years (IRR 1.18 vs ≥20 years old), female (IRR=1.13 vs male), young people residing outside of major cities (IRR 1.08 vs major cities) and Aboriginal and Torres Strait Islander young people (IRR 1.27 vs non-Indigenous).Conclusions ED mental health re-presentation is high among young people. We demonstrate factors associated with re-presentation that EDs could target for timely, high-quality care that is youth friendly and culturally safe, with appropriate referral pathways into community-based primary and mental healthcare services.